The Impact of Slow Stroke Back Massage on Blood Pressure among Hypertensive Patients - Anitasari, Tri Septi (Genius Journal, 2025)
Introduction: Hypertension is a prevalent non-communicable disease that contributes to serious health complications such as stroke, heart disease, and kidney failure. While pharmacological treatments are widely used, they may lead to drug-related problems, making non-pharmacological alternatives, such as Slow Stroke Back Massage (SSBM), increasingly relevant. Objective: This study aimed to determine the effect of Slow Stroke Back Massage therapy on reducing blood pressure in hypertensive patients. Method: A quantitative approach with a quasi-experimental, one-group pretest-posttest design was employed. The study was conducted at Dr. A. Dadi Tjokrodipo Hospital in Bandar Lampung from December 2024 to February 2025. A total of 21 hypertensive patients participated in the intervention, receiving SSBM therapy. Blood pressure measurements were taken before and after the intervention, and statistical analyses were performed to assess significance. Result: The mean systolic blood pressure decreased from 146.71 mmHg to 132.14 mmHg, and diastolic pressure also showed a reduction. The intervention resulted in statistically significant changes, with p-values of 0.000 for systolic and 0.003 for diastolic pressure, indicating the effectiveness of SSBM therapy. Conclusion: SSBM therapy significantly reduces both systolic and diastolic blood pressure in hypertensive patients. This intervention enhances relaxation, promotes vasodilation, and reduces sympathetic nervous activity. It is recommended that healthcare professionals consider integrating SSBM as a complementary therapy alongside pharmacological treatment for holistic hypertension management.